PENERAPAN MODEL MIND MAPPING UNTUK MENINGKATKAN KETERAMPILAN MENULIS RINGKASAN PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS TINGGI MI TARBIYATUL ISLAMIYAH - Tutus Rani Arifa; Jumiati Jumiati; Muhammad Fahmi Arifin (Jurnal Inovasi Penelitian, 2022)
The purpose of this study was to find out how the student’s summary writing skills were applied in high grades, namely in grades IV,V and VI at Mi Tarbiyatul Islamiyah, by applying the mind mapping model to the Indonesia language learning process. In this case the mind mapping model is a technique of taking notes thoroughly on one page and basically using visual images and other graphic feelings to form an impression on the brain. The formulation of the problem in this study are : 1) How is the application of the mind mapping model before and after being used in summary writing skills in Indonesia subjects in the high class of Mi Tarbiyatul Islamiyah, 2) Can the application of the mind mapping model improve summary writing skills in language subjects? Indonesia in the Mi Tarbiyatul Islamiyah High class with 126 students. The method used in this research is descriptive qualitative. The results in this study get an increase in summary writing skills at Mi Tarbiyatul Islamiyah. Judging from the stages in the application of the mind mapping model, it can be concluded that students can follow the predetermined interest generation, assimilation, organization and evaluation stages and produce a written work a creative, innovative and interesting mind mapping model